Шляхи і методи збереження представників родини Orchidaceae Juss. - Demidov, A.S.; Kolomeytzeva, G.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
The results of the modern state problems and perspectives analysis of family Orchidaceae Juss. representatives protection are cited. The problems of concervation of tropical and subtropical orchids ex situ are shown. The role of cryoconcervation orchid plants into the extremal environmental have been discution.